Singularity of the bryoflora in different urban landscapes and its value to the environmental quality in the city of São Paulo - Visnadi, Sandra Regina (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2022)
Urban parks allow to the public better understanding of the human action on the environment. Among such parks are the Previdência and Independência parks, where the bryophytes were studied in anthropic areas, heterogeneous forested areas, and in dense ombrophilous forest. The material (382 exsiccates), deposited in the herbariums of the Institute of Environmental Research and of the São Paulo City Hall, reveals a heterogeneous bryoflora (67 species) for the study area. The species richness, which is higher in dense ombrophilous forest (Previdência Park), lower in the anthropic area (Independência Park), and intermediate in heterogeneous forested areas (both parks), demonstrated the importance of bryoflora as environmental quality indicator in these locations. Richer brioflora for conspicuous and dense vegetation (Previdência Park) and the opposite for less wooded areas (Independência Park) confirms the afforestation is essential for the conservation of bryophytes in the urban parks of the city of São Paulo. More species are recorded for the area (Previdência Park) located in densely wooded region than for areas (Independência Park) in a more urbanized region, indicating that bryophytes are also useful for monitoring environmental quality in the city of São Paulo. The parks have endemic species from Brazil and an endangered species in the State of São Paulo.